AN EMPIRICAL ANALYSIS OF MARKETING MIX IN THE LIFE INSURANCE INDUSTRY TO PURCHASE DECISIONS OF LIFE INSURANCE PRODUCTS - Muhammad, Galuh Syailendra; Suciratin; Refan (STIE Kusuma Negara, 2019)
The marketing mix is ??very important and influences the marketing strategies of all companies, including the Life Insurance company. There are seven marketing mixes in the service industry such as Life Insurance companies, commonly known as 7P?s. This study aims to analyze the effect of product marketing mix, price, place, promotion, people, process and physical evidence that can influence decisions consumers in purchasing life insurance products. In conducting this research, a data collection method was used using a questionnaire using a sample of the population of DKI Jakarta residents who were working and earning income. The DKI Jakarta region was chosen as the research subject because it is considered as the most developed region with the highest level of community income compared to other regions in Indonesia and has the highest financial literacy index compared to other provinces in Indonesia; besides, Jakarta as the capital of the country has contributed to product penetration Life insurance. It is hoped that through this research the Life Insurance company knows in detail the extent to which the relationship between the product marketing mix, price, place, promotion, people, process, and physical evidence physical) and which of the marketing mix elements most influences the purchase decision of Life Insurance products that can be applied by Life Insurance companies to increase sales penetration of Life Insurance products.